2021
DOI: 10.1126/sciadv.abf0787
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the microenvironment around biosynthetic scaffolds in murine skin wound healing

Abstract: The structural properties of biomaterials play crucial roles in guiding cell behavior and influencing immune responses against the material. We fabricated electrospun membranes with three types of surface topography (random, aligned, and latticed), introduced them to dorsal skin excisional wounds in mice and rats, and evaluated their effects on wound healing and immunomodulatory properties. An overview of different immune cells in the microenvironment with the help of single-cell RNA sequencing revealed divers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 64 publications
4
79
0
Order By: Relevance
“…This is consistent with the results of a previous study indicating that the main composition of depilatory cream triggered the depilatory-induced, lipid-mediated skin inflammatory responses [ 38 ]. As reported, a dense and compact arrangement of hair follicles and sweat glands often indicates good wound healing [ 39 ]. The data suggested that sodium sulfide made a significant impact on healing, compared with depilatory cream and physical depilation methods.…”
Section: Discussionmentioning
confidence: 97%
“…This is consistent with the results of a previous study indicating that the main composition of depilatory cream triggered the depilatory-induced, lipid-mediated skin inflammatory responses [ 38 ]. As reported, a dense and compact arrangement of hair follicles and sweat glands often indicates good wound healing [ 39 ]. The data suggested that sodium sulfide made a significant impact on healing, compared with depilatory cream and physical depilation methods.…”
Section: Discussionmentioning
confidence: 97%
“…Appropriate blunt dissection is performed subcutaneously around the defect to ensure smooth implantation of the membrane underneath it. After that, the silicone splints and the defect circumference were fixed to ensure that the wound had no tension, and the healing was process under the condition of no stress [ 10 ]. Samples were then collected at 12 and 24 h for qPCR detection.…”
Section: Methodsmentioning
confidence: 99%
“…The inflammatory microenvironment makes it harder to conduct tissue engineering with biomaterials, thus elevates the importance of immune modulation to rebuild balance [5]. Macrophages, the dominant cells in FBR, whose transformation from pro-inflammatory towards pro-regenerative phenotype are vital in regeneration and wound healing after materials implantation [10]. If the material has the ability to adjust such interaction by providing suitable immune microenvironment, not only the pro-regenerative macrophage, but also the guidance of other cells that prompt to repair will accumulate in sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Each wound site was digitally photographed at the indicated time intervals, and the wound area was quantified using ImageJ software and was expressed as the percentage of the original wound size over time. Fourteen days after wounding, the mice were euthanized by cervical dislocation under anesthesia, and wound samples were harvested as follows: Using the residual wound as the center, a round skin sample (diameter, 10 mm) containing all the layers of skin was harvested [8]. In all mice, the left wound site was fixed in 4% formaldehyde for histological analysis, and the right wound site was immediately stored at −80 • C for further analysis.…”
Section: Full-thickness Excisional Wound Modelmentioning
confidence: 99%